Aplikasi Recovery Tidal Model dalam Pemberian Relaxation Therapy Pada Resiko Perilaku Kekerasan - Raphita Diorarta; Herni Susanti (Jurnal Keperawatan, 2021)
Emotional problems are a symptom of violent behavior. Interaction of nerve activity between the hypothalamus, limbic structures (amygdala and hyppocampus), and the higher cortical centers which are psychophysiological events of emotion in the human system. The purpose of this case study is to see the application of Tidal Model recovery in mental health in the provision of relaxation therapy. The search method used is a case study, and literature review. The author selects the analyzed journals to find the effectiveness of relaxation therapy against the risk of violent behavior and a journal on recovery that links therapeutic communication between nurses and patients. In the discussion of this paper, the sub-theme of therapeutic relationship between nurses and patients is found and also the self-awareness of patients who are part of the Tidal Model. By implementing relaxation therapy with the Tidal Model approach, there is a reduction in signs and symptoms in patients. Recommendations for nurses are able to become more empathetic nurses in implementing therapy and can support and encourage patient awareness in carrying out therapies that will bring patients into recovery.